2010
DOI: 10.1603/033.047.0102
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships Among Species of <I>Lutzomyia</I>, Subgenus <I>Lutzomyia</I> (Diptera: Psychodidae)

Abstract: Lutzomyia França is the largest and most diverse sand fly genus in the New World and contains all the species involved in the transmission of American visceral leishmaniasis (AVL). Morphological characters were used to test the monophyly and to infer phylogenetic relationships among members of the Lutzomyia subgenus. Fifty-two morphological characters from male and female adult specimens belonging to 18 species of Lu. (Lutzomyia) were scored and analyzed. The resulting phylogeny confirms the monophyly of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Previously, systematic classification has been largely based on morphology of the New World (Young & Duncan, ; Galati, ) and Old World species (Rispail & Léger, ,), and molecular analyses of Phlebotominae as a whole are generally lacking. Although several comparative molecular analyses exist, many are restricted to specific subgenera (Di Muccio et al , ; Esseghir & Ready, ; Pinto et al , ; Cohnstaedt et al , ). Nonetheless, our phylogeny here does allow for limited comparisons against previous hypotheses, some of which receive additional support here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, systematic classification has been largely based on morphology of the New World (Young & Duncan, ; Galati, ) and Old World species (Rispail & Léger, ,), and molecular analyses of Phlebotominae as a whole are generally lacking. Although several comparative molecular analyses exist, many are restricted to specific subgenera (Di Muccio et al , ; Esseghir & Ready, ; Pinto et al , ; Cohnstaedt et al , ). Nonetheless, our phylogeny here does allow for limited comparisons against previous hypotheses, some of which receive additional support here.…”
Section: Discussionmentioning
confidence: 99%
“…Phlebotominae systematics has drawn the attention of such luminaries as Graham Fairchild (Fairchild, 1955) and Willi Hennig (Hennig, 1972), and in recent years they have been the subject of some molecular studies (Depaquit et al, 1998(Depaquit et al, , 2000a(Depaquit et al, ,2000b(Depaquit et al, , 2004Esseghir & Ready, 2000;Aransay et al, 2000b;Beati et al, 2004;reviewed by Depaquit, 2014). Morphological data continue to be used and are the basis of the most inclusive phylogenies, and such analyses still tend to use terminal sets that are restricted to the Old or New World (Galati, 1995(Galati, , 2010(Galati, , 2014Rispail & Léger, 1998a,1998bIlango, 2004;Pinto et al, 2010). Thus relationships within the family as a whole remain in question.…”
Section: Introductionmentioning
confidence: 99%
“…In South America, the genus Lutzomyia is suspected of containing multiple cryptic species (Young and Duncan 1994, Dujardin et al 2005, Pinto et al 2010, complicating the production of a deÞnitive key. Lutzomyia whitmani (Antunes and Coutinho) has been proposed to be a cryptic species complex within a relatively small geographic in Brazil (Rangel et al 1996, Margonari et al 2004).…”
mentioning
confidence: 99%
“…(19) The last one, as a consequence of natural hybridisation, might make the species to share traits of biomedical importance like vector competence, insecticide resistance, behavioral phenotypes and environmental adaptability, highlighting the need to focus on gene flow and the distribution of phenotypes of biomedical importance. (29) Pinto et al (30) suggested that the phylogenetic proximity among Lutzomyia subgenus is congruent with their role as vectors of the same parasite; given that the physiologic mechanisms of these insects are likely to be similar due to recent common ancestry. Although Lu.…”
Section: Discussionmentioning
confidence: 99%